Superposition based direct downlink channel state information feedback method - XU Dao-feng 1; HUANG Yong-ming1; YANG Lv-xi1 (Tongxin xuebao)
A low cost, real-time feedback method for downlink channel state information （DL-CSI） was proposed. DL-CSI was superimposed with uplink user sequences （UL-US） before transmission and thus exclusive occupation of system resources could be avoided. With guaranteed UL-US SER performance and DL-CSI estimation accuracy, higher spectral efficiency could be achieved by sacrificing some UL-US’s symbol error rate （SER） performance. Due to spreading processing, DL-CSI could be accurately recovered even with little allocated energy. Simulations demonstrated the practicability of the proposed method.